Efektivitas Pelatihan Kebersyukuran untuk Meningkatkan Kesejahteraan Subjektif pada Penderita Hipertensi - Anisa Rahmanita; Qurotul Uyun; Rr. Indahria Sulistyarini (JIP (Jurnal Intervensi Psikologi), 2016)
The purpose of this study is to examine the effectiveness of gratitude training in increasing life satisfaction and affection level of hypertentive patient. The participants of this study were patients who had hypertention, 40-60 years old, and muslim. The design of this study is quasi-experimental design, wtihpretest-posttest control group desain Data were collected with Subjective well-being Scale (SWLS) from iener, Emmon, Larsen, and Griffin (1985) and The Positive and Negative Affect Schedule (PANAS) from Watson, Clark, and Tellegen (1988). Analysis data showed that there was a significant difference betweenSWLS score of experiment and control group (t=9.624, p = 0.000 p< 0.01) and PANAS score (t=10.931, p= 0.000 p<0.01).Key words : gratitude training, subjective well-beling, life satisfaction, affection, hypertention